TRADISI REBO WEKASAN DI KAMPUNG SAMBIRATA, KECAMATAN CIBEBER DALAM PERSPEKTIF LIVING HADIS - Anzil Alaina Maidah; Albarra Gilang Andika; Muhammad Alif (CV. Adiba Aisha Amira, 2026)
This study examines the Living Hadith phenomenon through the Rebo Wekasan tradition in Sambirata Village, Cibeber District, Cilegon. Rebo Wekasan is a religious practice performed on the morning of the last Wednesday of the Hijri month and is understood by the community as a spiritual effort to seek protection from calamities. This research employs a qualitative method with a Living Hadith approach. Data were collected through in-depth interviews, participatory observation, and documentation. The findings indicate that the Rebo Wekasan ritual consists of the sunnah prayer of warding off misfortune, collective supplications, almsgiving, and the recitation of salawat. Although this tradition is not based on explicit textual hadith, it is perceived as a positive religious practice that strengthens social solidarity and religious identity within the community.